Invisible among the vulnerable: a nuanced perspective of energy poverty at the intersection of gender and disability in South Africa - Michael Adu Okyere; Boqiang Lin (Humanities & Social Sciences Communications, 2023)
Abstract This study addresses a crucial gap in the existing literature by exploring the intricate relationship between gender, disability, and energy poverty. While prior research has shown that females and persons with disabilities are more vulnerable to energy poverty, our study adopts an intersectionality framework to investigate how these identities interact with other variables, including life dissatisfaction, food insecurity, and energy subsidy, to shape the experience of energy deprivation. Using a series of robust techniques, our analysis of the General Household Survey in South Africa reveals several noteworthy findings. First, while females are less likely to be energy poor, the intersection between females and disability significantly amplifies their risk of energy poverty by 2.6%. Our mediation analysis further elucidates that life dissatisfaction and food insecurity serve as critical mechanisms through which this intersection exacerbates energy poverty. Importantly, we also find that the impact of energy subsidy is most effective when targeted toward females with disabilities, highlighting the need for tailored interventions. We call for policymakers and stakeholders to prioritize targeted energy subsidy schemes for persons with disabilities and females, recognizing the critical role such policies can play in mitigating energy poverty and promoting equity.